Sustainbility of the Small Industrial Sector in The Face of Increasing BBM in Indonesia - Nurul haeriyah Ridwan (Jurnal Economic Resource, 2023)
The assessment of various parties is that the government has not implemented a plan that can minimize the impact of the increase in subsidized fuel prices, the transfers carried out prioritize only social interests, so that weak market mechanisms must be taken seriously. This is certainly homework for the industrial sector to immediately take appropriate action regarding the impact of rising fuel prices. The types of research data collected are primary data obtained through direct observation and surveys as well as secondary data in the form of reports from each relevant SME department and data through case studies and comparative studies through reviews of previous research and policy references, in order to obtain sufficient data. and accountable. Case studies are carried out on SME target objects according to predetermined criteria. Based on the research results, it was found that the turnover of the two MSME respondents in the food and beverage sector was reduced because of the fuel price increase policy. The food and beverage cost variables for MSMEs most affected by the increase in subsidized fuel are as follows: (1) Transportation costs (2) Raw material costs (3) Capital costs.